Application of Activators Ecarin and Factor Xa in Thrombelastography for Measurement of Anticoagulant Effect of Direct Oral Anticoagulants Using TEG 5000 - Artang, Ramin; Brod, Camille; Nielsen, Jorn Dalsgaard (Seminars in Thrombosis and Hemostasis, 2022)
There are situations where monitoring direct oral anticoagulants (DOACs) would be useful, including bleedings and trauma. The thromboelastographic technique has proven useful in bleeding situations in trauma and heart surgery. The aim of this study was to examine the effect of DOACs on all currently commercially available conventional TEG®5000 assays as well as novel modified assay using Ecarin and human factor Xa (HFXa). Healthy male volunteers were given single dose of oral dabigatran 150 mg, rivaroxaban 20 mg, or apixaban 5 mg. Kaolin, RapidTEG, functional fibrinogen, PlateletMapping assay, and novel modified assays using Ecarin and HFXa were prepared. All TEG parameters were recorded. DOAC concentrations were correlated to the parameters with highest response to the DOAC effect. Sensitivity and negative predictive value of the parameter with highest response to DOAC concentration of 50 ng/mL was calculated. None of the conventional TEG assays demonstrated significant response to the effect on apixaban. Using Ecarin, reaction time R was strongly correlated with dabigatran concentrations. Using HFXa assay, R was strongly correlated with rivaroxaban and apixaban concentrations: r = 0.96, 0.84, and 0.86, respectively; p < 0.0001 for all. The R times obtained with the modified assays demonstrated strong sensitivity and negative predictive values for DOAC levels of ≥50 ng/mL. We have demonstrated that TEG®5000 can monitor the DOAC effect on hemostasis when the appropriate activator is used with significant correlation with DOAC concentrations. Larger clinical studies are warranted for correlation of TEG profile and clinical outcomes.
Keywords: thrombelastography; direct oral anticoagulants; platelets; dabigatran; rivaroxaban; apixaban